THE INFLUENCE OF USING FUNDAMENTAL AND TECHNICAL ANALYSIS ON SHARE PRICES - redha romadi putra, firdaus gusti; Wuryani, Eni (Ekspektra : Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the effect of the variables contained in fundamental and technical analysis of stock prices. Variables used include Earning Per Share, Return On Assets, Book Value Per Share, Price to Book Value, Past Share Prices, Dup and Ddown. Sample selection uses saturated samples by using all food and beverage companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The data analysis technique used is regression analysis using SPSS 23. The results of the study show that simultaneously all variables affect the stock price. Partially Earning Per Share, Price to Book Value, Past Share Prices, and Ddown have a significant effect on stock prices, while Return On Assets, Book Value Per Share, and Dup have no significant effect on stock prices.